Synthesis and derivatization of expanded [n]radialenes (n=3, 4) - Gholami, Mojtaba; Ramsaywack, Sharwatie; Chaur, Manuel N.; Murray, Adrian H.; Mcdonald, Robert; Ferguson, Michael J.; Echegoyen, Luis; Tykwinski, Rik (Chemistry - A European Journal, 2013)
Versatile, iterative synthetic protocols to form expanded [n]radialenes have been developed (n=3 and 4), which allow for a variety of groups to be placed around the periphery of the macrocyclic framework. The successful use of the Sonogashira cross-coupling reaction to complete the final ring closure demonstrates the ability of this reaction to tolerate significant ring strain while producing moderate to excellent product yields. The resulting radialenes show good stability under normal laboratory conditions in spite of their strained, cyclic structures. The physical and electronic characteristics of the macrocycles have been documented by UV-visible spectroscopy, electrochemical methods, and X-ray crystallography (four derivatives), and these studies provide insight into the properties of these compounds as a function of pendent substitution in terms of conjugation and donor/acceptor functionalization. Feeling the strain: By using a handful of versatile building blocks, expanded radialenes are easily assembled through Sonogashira cross-coupling reactions. X-ray crystallography shows expanded [3]radialenes have a rather significantly strained enyne framework, whereas those of the expanded [4]radialenes show much less strain (see figure). © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.